Optimizing the META Mangrove ecosystem transformation approach model in improving the sustainability of mangrove ecotourism and empowering the blue economy in East Java - Riyanto, Darwin Yuwono; Santoso, Rudi; Wibowo, Januar; Arifin, Mochammad (Edelweiss Applied Science and Technology, 2025)
This study aims to examine and optimize the Mangrove Ecosystem Transformation Approach (META) model to enhance the sustainability of mangrove ecotourism and empower the blue economy in East Java, Indonesia. Employing a mixed-method approach, both qualitative and quantitative data were collected through in-depth interviews, field observations, and structured surveys involving key stakeholders, including local communities, government officials, and ecotourism operators. Data analysis was conducted using Structural Equation Modeling (SEM-PLS) to test the hypothesized relationships. The results reveal that the driver variable (X1) significantly influences ecotourism sustainability (Y) both directly and indirectly, with the mediation variable (MED) playing a critical role in strengthening this relationship. Specifically, the path coefficients (0.560 from X1 to MED and 0.870 from MED to Y) indicate that ecosystem transformation through product innovation, community capacity building, and marketing technology integration has a greater sustainable impact compared to direct intervention alone. The study further demonstrates that multi-stakeholder collaboration and embedding sustainability values across the entire ecotourism value chain are essential for long-term success. Theoretically, this research bridges the gap between sustainable ecotourism, destination marketing, and blue economy literature, offering an adaptable and replicable framework for other coastal destinations. Managerially, it provides actionable strategies for policymakers, destination managers, and local communities to develop mangrove ecotourism initiatives that conserve ecosystems while improving livelihoods.